Complications and outcomes of SARS-CoV-2 in pregnancy: where and what is the evidence?. (2nd July 2020) - Teles Abrao Trad, Ayssa; Ibirogba, Eniola R.; Elrefaei, Amro; Narang, Kavita; Tonni, Gabriele; Picone, Olivier; Suy, Anna; Carreras Moratonas, Elena; Kilby, Mark D.; Ruano, Rodrigo
ABSTRACT: Objectives: To add to the growing evidence on SARS-CoV-2 infection during pregnancy, so as to better inform clinical decision making and optimize patient outcomes. Methods: A systematic search of relevant databases was perfomed on 25 March 2020 and a repeat search, on 10 April 2020. Reports of pregnant patients with SARS-CoV-2 infection at any time during their pregnancy were reviewed and summarized . Results: We summarized the outcomes of a total of 155 pregnant women and 118 neonates. The evidence suggests a similar rate of severe COVID-19 cases in pregnant women and the general population. The frequency of cesarean deliveries is high, against guidelines recommendations. Conclusion: Limited data on COVID-19 during preganacy, associated with a wide variation in the methodology make accurate data interpretation difficult.